Juridical Analysis of Legal Protection of Medical Personnel Victims of Persecution in Providing Health Services (Analysis of Supreme Court Decision No. 779.PID. B/2014/PN. JKT. PST) - Liem, Simon Yosonegoro; Sembiring, Tamaulina Br. (Jurnal Ekonomi, 2024)
This research aims to analyze legal protection for medical personnels who are victims of abuse in providing health services. This research method is normative by reviewing statutory regulations. The technical analysis of legal materials used is descriptive-qualitative. The research results show that (i) Law no. 17 of 2023 about Health includes a fairly comprehensive legal framework regarding legal protection for doctors who experience abuse while providing health services in Indonesia, but there are several challenges in its implementation, (ii) abuse of medical personnel is a crime and the causes of crime are problems. which are complex, especially influenced by emotional and environmental factors, (iii) doctors should receive legal protection if the doctors followed the standard operating procedures.